Resistance exercise reduced the expression of fibroblast growth factor-2 in skeletal muscle of aged mice - Jin-Soo Kim; Dong Hyun Yoon; Hee-jae Kim; Mi-jung Choi; Wook Song (Integrative Medicine Research, 2016)
Background: Fibroblast growth factor-2 (FGF-2) protein level has been shown to be elevated in aged mice muscle compared to adult mice. It activates the satellite cell quiescence, which leads to satellite cell depletion and may accelerate aging process. The purpose of this study was to see the effect of resistance exercise on skeletal muscle FGF-2 protein level in aged mice. Methods: This study included eight young adult control C57BL/6 male mice (age 12 weeks, YCON group) and 14 aged C57BL/6 male mice (age 19 months), randomly divided into two groups (old control, OCON, n = 7; old resistance exercise, ORT, n = 7). Resistance ladder climbing exercise was conducted 3 d/wk for 12 weeks. Soleus and tibialis anterior muscles were collected for body composition, relative grip strength, and muscle wet weight and for enzyme-linked immunosorbent assay protein analysis. Results: Relative soleus muscle wet weight and hindlimb lean mass showed a significant increase in ORT group compared to OCON group (p = 0.013 and p = 0.015, respectively). In relative grip strength, both OCON and ORT showed a significant decrease compared to YCON (p < 0.001 and p = 0.011, respectively). However, ORT showed a significant increase compared to OCON (p = 0.02). OCON showed a significant increase in skeletal muscle FGF-2 protein level compared to YCON in soleus (p = 0.035), and ORT showed a significant decrease compared to OCON in soleus muscle (p = 0.045). FGF-2 protein level was significantly decreased in tibialis anterior muscle in the ORT group compared to OCON (p = 0.022). Correlation analysis showed a negative correlation between FGF-2 protein level and soleus and tibialis anterior muscle weight (r2 = 0.514, p = 0.0035; r2 = 0.312, p = 0.025, respectively). Conclusion: Twelve weeks of resistance exercise reduced soleus and tibialis anterior muscle FGF-2 protein level in aged mice with improvement in appendicular lean mass and muscle strength. Thus, resistance exercise could be an efficient intervention for preventing age-related increase of FGF-2 in skeletal muscle.